Applying the EFQM Model for Evaluating the Performance: A Case Study in a Public Hospital - Salah Addin Asadi; Saeed Hosseini Bargzan; Mobin Sokhanvar (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Evaluation is a key process to improve the organization. The maintenance and improvement of the health is the priority of the people of each country these days. Ensuring the provision of appropriate services requires the evaluation of the health system performance. European Foundation for Quality Management (EFQM) model is a self-assessment model and allocates more for health and care organizations and almost evaluates an organization in all structural and functional aspects. This study was conducted with to the aim of evaluating the performance of a public hospital in Tabriz according to the model of Europe Foundation for Quality Management. Methods: This study was a cross - sectional study in 2015 in a public hospital in Tabriz. Data collection tools had been standard questionnaire of Europe Foundation Model for Quality Management. Data was gathered through standard and prestigious questionnaire of Europe Foundation Model for Quality Management which consisted of 90 questions, same in the field of nine criteria. After visiting the hospital by experts, meeting was hold among them and proceeded to consult and complete the questionnaire. The data was reported by descriptive tests and software of EXCELL was used for data analysis. Results: The mean score of performance evaluation in terms of leadership was 73.6 points out of 100 points, in terms of policy and strategy, 46.8 points out of 80, in terms of human resources 54.1 out of 90 points, in terms of strategies and policy 41.9 points out of total 90 points, in terms of processes 59.8 points out of 140 points, 66 points out of 200 in terms of customer results, in terms of human resources results 23.76 points out of a total of 90 points, 40.2 points out of a total of 60 points, in terms of society results and in terms of key performance the result was 71.35 points out of 150 points . The average total score of 477 points out of 1000 points was performance evaluation. The results of the report are 47.75%. Finally, the results showed that the hospital had relatively appropriate status. Conclusion: The findings showed the need for more attention to human resources and customer results. Enhancing employee's satisfaction factors to increase their satisfaction and efficiency, identifying foreign customers, categorizing and measuring different needs of patients in order to response and upgrade the system of addressing the complaints through the reform the processes are those cases that are proposed to improve the organization and increase compliance with organizational excellence model .